Partial coding algorithm for area and energy efficient crosstalk avoidance codes implementation. Issue 2 (1st March 2014) - Halak, Basel
Abstract : Modern interconnect performance is greatly affected by crosstalk noise because of continuous decrease in wire separation and increase in its aspect ratio with technology scaling. Such noise is highly dependent on data transition patterns, coding techniques have been proposed to alleviate crosstalk delay by controlling these patterns. The complexity of available crosstalk avoidance codes, along with their associated overheads, increase rapidly with bus width. The lack of energy and area‐efficient method to implement such codes has so far prevented their use in practical designs. This study presents a generic framework, which allows efficient implementations of crosstalk avoidance codes; the essence of the proposed approach is based on the partial coding concept. Quantitative analysis performed in 32 nm technology shows that substantial savings in area and energy costs can be obtained using the proposed technique compared with both existing coding solutions and conventional methods as shielding and repeater insertion.